2020
DOI: 10.31234/osf.io/djteh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptation aftereffects reveal how categorization training changes the encoding of face identity

Abstract: Previous research suggests that learning to categorize faces along a novel dimension changes the perceptual representation of such dimension, increasing its discriminability, its invariance, and the information used to identify faces varying along the dimension. A common interpretation of these results is that categorization training promotes the creation of novel dimensions, rather than simply the enhancement of already-existing representations. Here, we trained a group of participants to categorize faces tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 55 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…The tuning functions used by the brain to encode such dimensions might be different than what is represented by the standard population model used here. For example, face features are thought to be encoded through monotonic tuning functions (e.g., sigmoidal; see [5,45,43]). Using computational modeling and visual adaptation, it has been found that the effects of categorization on perception of face identities along the category-relevant dimension [59,60,61] can be best explained using a specific gain mechanism [45].…”
Section: Re-interpreting Results In the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…The tuning functions used by the brain to encode such dimensions might be different than what is represented by the standard population model used here. For example, face features are thought to be encoded through monotonic tuning functions (e.g., sigmoidal; see [5,45,43]). Using computational modeling and visual adaptation, it has been found that the effects of categorization on perception of face identities along the category-relevant dimension [59,60,61] can be best explained using a specific gain mechanism [45].…”
Section: Re-interpreting Results In the Literaturementioning
confidence: 99%
“…For example, face features are thought to be encoded through monotonic tuning functions (e.g., sigmoidal; see [5,45,43]). Using computational modeling and visual adaptation, it has been found that the effects of categorization on perception of face identities along the category-relevant dimension [59,60,61] can be best explained using a specific gain mechanism [45]. It is currently unknown exactly how the complex shape and object stimuli used in some studies are encoded, but encoding that is different from that of orientation might be at the heart of the results obtained with such dimensions.…”
Section: Re-interpreting Results In the Literaturementioning
confidence: 99%
See 2 more Smart Citations